Analysis of Junior High School Students' Numeracy Literacy with Various Levels of Mathematical Curiosity - Husain, Dayana Sabila; Salido, Achmad; Aswin, Aswin; Meiliati, Rafika (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2025)
Numerical literacy is an essential competency in education, yet the results of the 2022 Programme for International Student Assessment (PISA) indicate that most Indonesian students still have low numerical literacy skills. One factor suspected to contribute to this issue is mathematical curiosity. This study aims to analyze students' numeracy literacy skills based on their levels of mathematical curiosity. A descriptive qualitative approach was employed, with research subjects selected through purposive sampling at a junior high school in Kolaka Regency, Southeast Sulawesi. Data were collected through a mathematical curiosity questionnaire and an open-ended numeracy literacy test. The data analysis process involved reduction, presentation, and conclusion drawing. The results indicate that students with a high level of mathematical curiosity exhibit better numeracy literacy skills than those with moderate or low curiosity. They can explore information in depth, recognize patterns, and apply appropriate strategies to solve problems. Students with moderate curiosity demonstrate a good understanding of numeracy but require further encouragement to present a more comprehensive problem-solving process. Meanwhile, students with low curiosity tend to be less engaged in problem exploration and in providing thorough solutions. These findings reinforce the significant role of curiosity in strengthening numeracy literacy.